18.2k views
1 vote
The angle measure of thre angle of a triangle are p, q and r. Angle measure of q is one third of p and r is the difference of p and q.

2 Answers

3 votes

The angle measure of three angle of a triangle are p, q and r.

As, sum of angles of triangle is 180 degrees.

So, p+q+r=180

Angle measure of q is one third of p

q=
(1)/(3)p

r is the difference of p and q

r=p-q

As, q=
(p)/(3)

So, r=p-q=p-
(p)/(3)

r=
(3p)/(3)-(1p)/(3)

r=
(3p-1p)/(3)

r=
(2p)/(3)

As, p+q+r=180 and q=
(p)/(3) and r=
(2p)/(3)

So, we get

p+
(p)/(3)+
(2p)/(3)=180

To get rid of fraction, let us multiply the complete equation by 3

3*p+ 3*
(p)/(3)+ 3*
(2p)/(3)=3*180

3p+p+2p=540

6p=540

To solve for p, let us divide by 6 on both sides


(6p)/(6) =(540)/(6)

p=90

As, p=90

So, q=
(p)/(3)

q=
(90)/(3)

q=30

And, r=
(2p)/(3)

r=
(2*90)/(3)

r=
(180)/(3)

r=60

So, p=90, q=30, r=60

The three angles of triangle are 90,30 and 60

User XWang
by
5.5k points
4 votes

In this question, i think we have to determine all the three angles of a triangle.

Since the three angles of a triangle are p,q and r.

Since, angle measure of q is one third of p, which implies


q=(p)/(3)

Angle measure of r is the difference of p and q, which implies


r=p-q (Equation 1)

By using the angle sum property of a triangle which states that the sum of all the angles of a triangle is
180^(\circ)

p+q+r=
180^(\circ)

Substituting the value of r from Equation 1,

p+q+p-q=
180^(\circ)

2p=
180^(\circ)

p=
90^(\circ)

Since
q=(p)/(3)


q=(90)/(3) = 30^(\circ)

Since, r=p-q

r =
90^(\circ)-30^(\circ)=60^(\circ)

User Santiago Arizti
by
5.6k points